Pemberdayaan UMKM Pangan Lokal Ikan Kurisi Sebagai Upaya Pencegahan Stunting di Desa Pabean - Zirli Afida Rossa; Aufa Izzudin Baihaqi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Stunting is still a serious health problem in Indonesia. According to the 2022 National Nutritional Status Survey (SSGI), the stunting rate in Indonesia reached 21.6%. The factors causing stunting are very diverse, in addition to socioeconomic factors, also caused by knowledge about the fulfillment of balanced nutrition which is still lacking and also poor food processing methods. The purpose of this community service is to increase public understanding of the importance of adequate nutritional value in food and encourage MSME innovation that uses regional superior commodities as an alternative to meet balanced nutrition in the community and as MSME innovation in this field. The method used is qualitative, with data collection through observation, interviews and documentation. The results of this community service activity show the increasing understanding of the people of Pabean Village on the importance of balanced nutrition for pregnant, lactating and child women and the increase in innovation of the Pabean Village community in processing kurisi fish in the context of stunting prevention, as well as the potential of MSMEs in this field.